Can Online Delivery Increase Acces to Education? - Joshua S. Goodman; Julia Melkers; Amanda Pallais (Center for Economic Studies and ifo Institute (CESifo), 2017)
Though online technology has generated excitement about its potential to increase access to education, most research has focused on comparing student performance across online and in-person formats. We provide the first evidence that online education affects the number of people pursuing formal education. We study the Georgia Institute of Technology's Online M.S. in Computer Science, the earliest model to combine the inexpensive nature of online education with a highly-ranked degree program. Regression discontinuity estimates exploiting an admissions threshold unknown to applicants show that access to this online option substantially increases overall enrollment in formal education, expanding the pool of students rather than substituting for existing educational options. Demand for the online option is driven by mid-career Americans. By satisfying large, previously unmet demand for mid-career training, this single program will boost annual production of American computer science master's degrees by about seven percent. More generally, these results suggest that low-cost, high-quality online options may open opportunities for populations who would not otherwise pursue education.
Keywords: I20; J00; 330; online education; computer science